Tao Analysis: Exercise 2.2.1
This is a proof of the associative property of natural number addition.
We will show that for any natural numbers $$ a, b, and\, c $$ ,
we have $$ (a+b)+c = a+(b+c) $$ .
Therefore, $$ (a+b)+0=a+(b+0) $$ , proving the base case.
The induction is closed. Therefore, $$ (a+b)+c=a+(b+c) $$ for all natural numbers $$ a, b, and\,c $$ .
To show this, let's induct on
$$ c=0 $$ | Assumed |
$$ b+0=b $$ | Lemma 2.2.2 |
$$ (a+b)+c=(a+b)+0 $$ | Substitution |
$$ =a+b $$ | Lemma 2.2.2 |
$$ =a+(b+0) $$ | Substitution |
Now, the inductive case.
Here we are assuming that
$$ (a+b)+(c++)=(c++)+(a+b) $$ | Commutative property |
$$ =(c+(a+b))++ $$ | Definition of addition |
$$ =((a+b)+c)++ $$ | Commutative property |
$$ =(a+(b+c))++ $$ | Inductive hypothesis |
$$ =((b+c)+a)++ $$ | Commutative property |
$$ =((b+c)++)+a $$ | Definition of addition |
$$ =((c+b)++)+a $$ | Commutative property |
$$ =((c++)+b)+a $$ | Definition of addition |
$$ =a+(b+(c++)) $$ | Commutative property x2 |
Comments
Post a Comment